TOWARDS OPERATIONALIZING WHITE MALE ACCOUNTABILITY IN ARTIFICIAL INTELLIGENCE DEVELOPMENT INTERROGATING IMPACTS OF AND SOLUTIONS TO OVERREPRESENTATION UTILIZING RELATIONAL ETHICS FRAMEWORKS - Doyle, Dylan Thomas (AoIR Selected Papers of Internet Research, 2021)
Numerical metrics demonstrate that white men are demographically overrepresented in Artificial Intelligence (AI) technology development, research, and media coverage. This overrepresentation creates immediate and downstream harms that corporations and technologists in industry and the academy alike must contend with to ensure the creation of AI technologies, AI development organizations, and AI research institutions that are ethical, fair, accountable, transparent, and beneficial to all people. After defining the problem of overrepresentation and exploring why this problem is vital to address, this paper will posit a two-pronged theoretical solution to be implemented: (1) increasing white male accountability in AI technology spaces and (2) moving away from an underlying utilitarian or deontological ethical foundation and towards a relational ethical foundation. Using that theoretical analysis the paper will then present a model for taking this two-pronged theoretical solution from theory into practice by providing specific recommendations for operationalizing the proposed framework at the levels of AI technology development.